Osteology of a New Specimen of Macrocnemus aff. M. fuyuanensis (Archosauromorpha, Protorosauria) from the Middle Triassic of Europe: Potential Implications for Species Recognition and Paleogeography of Tanystropheid Protorosaurs - Jaquier, Vivien P.; Fraser, Nicholas C.; Furrer, Heinz; Scheyer, Torsten M. (Frontiers in Earth Science, 2017)
Over the past two decades, a wealth of marine and terrestrial reptiles, including protorosaurian archosauromorphs, has been described from Triassic shales and limestone layers in southern China. Recovered from the eastern margin of the Tethys Ocean, these forms often show remarkable similarities to taxa that were previously known and described from Europe, i.e., the western Tethyan margin. One protorosaurian that is known from the western and the eastern Tethyan province is the genus Macrocnemus, with currently three recognized species: 1) M. bassanii from the Middle Triassic Besano Formation and Meride Limestone (late Anisian – early Ladinian), UNESCO World Heritage Site Monte San Giorgio, Ticino, Switzerland; 2) M. obristi from the Prosanto Formation (early Ladinian) of the Ducan area, Grisons, Switzerland; and 3) M. fuyuanensis from the Falang Formation (Ladinian), Yunnan Province, southern China. Recently a new specimen, PIMUZ T 1559, from the upper Besano Formation at Meride, Ticino, Switzerland, was prepared, revealing a disarticulated skeleton which includes most of the cranium and lower jaw, pre-caudal vertebral column and ribs, the forelimbs, and girdle elements. Unambiguously assignable to the genus Macrocnemus, it evinces particularly gracile elongated cervical ribs, as well as a humerus/radius ratio that is comparable only to that of M. fuyuanensis from southern China. Based on this feature we tentatively recognize the new specimen as M. aff. fuyuanensis from Europe. The position and exquisite preservation of the clavicle and interclavicle in this specimen allows a revision of the shoulder girdle of Macrocnemus when articulated, which also has implications for closely related protorosaurian taxa, such as the long-necked Tanystropheus. Furthermore, differences in the shape and morphology of the interclavicle including pointed wing-like lateral processes and a short, fusiform caudal process represent rare discrete characters that allow separation of the specimens of M. bassanii from the new specimen of M. aff. fuyuanensis.